Analisis Kualitatif Penggunaan Background Seragam pada Online Meeting - Rafi Audian; Diah Priharsari; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
This time, various kinds of activities can be carried out more easily because of the rapid development of technology. The example is when communicating between humans in the world, communication activities can be carried out more easily by using online meeting applications such as Zoom and Google Meet. The application is widely used to conduct video conferences or online meetings because it is easy to use and also had some of interesting features. One of the interesting feature is the feature to change the background of the user's camera view. The feature to change the background is widely used during webinars, work meetings, distance learning, or during other activities that use video conferencing applications or online meetings. In this study, a qualitative analysis will be carried out to determine the background of the use of uniform backgrounds in online meetings and also the views of the online meeting committee on the use of uniform backgrounds. This study involved 21 sources to collect data using interviews. The data that has been collected will be processed using the thematic coding analysis method. From the results of this study, it was found that there were five aspects that became the view of the online meeting committee on the use of uniform backgrounds and six aspects behind the use of uniform virtual backgrounds.